1991
DOI: 10.1177/014616729101700204
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Jury Dogmatism on Reactions to Jury Nullification Instructions

Abstract: Jury nullification instructions give jurors permission to disregard a law if they feet that its strict application would result in an unjust verdict. In a jury simulation, dogmatic and nondog matic juries were given either standard or null fication instruc tions by the judge after hearing a euthanasia trial. Because of their alleged respect for and reliance on the pronouncements of authority figures, it was hypothesized that dogmatic juries would be more influenced than nondogmalic juries by the type of judge'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Jury nullification. Four studies have examined the impact of explicitly reminding juries of their right to disregard the evidence and "nullify" a law that seems unfair (Horowitz, 1985(Horowitz, , 1988Kerwin & Shaffer, 1991;Niedermeier, Horowitz, & Kerr, 1999). The primary finding from these studies is that reminding juries of their nullification capability makes them more likely to use it.…”
Section: Procedural Characteristicsmentioning
confidence: 99%
“…Jury nullification. Four studies have examined the impact of explicitly reminding juries of their right to disregard the evidence and "nullify" a law that seems unfair (Horowitz, 1985(Horowitz, , 1988Kerwin & Shaffer, 1991;Niedermeier, Horowitz, & Kerr, 1999). The primary finding from these studies is that reminding juries of their nullification capability makes them more likely to use it.…”
Section: Procedural Characteristicsmentioning
confidence: 99%
“…A series of research studies have previously investigated the court's assumption regarding the influence of jury nullification instructions on the manner in which jurors both evaluate evidence and arrive at culpability judgments in criminal and civil cases (Hill & Pfeifer, 1992;Horowitz, 1985Horowitz, , 1988Kerwin & Shaffer, 1991;Niedermeier, Horowitz, & Kerr, 1999;Pfeifer, Brigham, & Robinson, 1996). Empirical studies have generally found a tendency for nullified juries to operate on their sentiments of justice and fairness, including reliance upon highly prejudicial beliefs.…”
Section: Influence Of Jury Nullification Instructionsmentioning
confidence: 99%
“…For example, several studies have shown that jury nullification instructions are not a prerequisite for jurors to abandon proper application of the law such that they might instead apply their own personal notions of justice (also referred to as commonsense justice) (Finkel, 1995;Finkel, Hurabiell, & Hughes, 1993;Smith, 1991). Other studies previously discussed have examined only the predicted direction of guilt judgments under nullification instruction conditions as evidence for the influence of public attitudes (Hill & Pfeifer, 1992;Horowitz, 1985Horowitz, , 1988Kerwin & Shaffer, 1991;Niedermeier et al, 1999;Pfeifer et al, 1996). As alluded to previously, it is important that we seek to understand the manner in which personal attitudes are accessed and applied in juridic decision-making.…”
Section: Attitudes and Jury Nullificationmentioning
confidence: 99%
See 1 more Smart Citation
“… 76. For discussion of jury deliberations generally see, e.g., Devine (2012: 152–180). For research suggesting deliberation has positive affects on juror bias see, e.g., Kaplan and Miller (1978); London and Nunez (2000); Kerwin and Shaffer (1991). …”
mentioning
confidence: 99%